Magnetic anomalies in Fe-doped NiO nanoparticle. (22nd September 2017) - Pradeep, R; Gandhi, A C; Tejabhiram, Y; Mathar Sahib, I K Md; Shimura, Y; Karmakar, L; Das, D; Wu, Sheng Yun; Hayakawa, Y
Abstract: Undoped and iron-doped NiO nanoparticle were synthesized by standard hydrothermal method. A detailed study is carried out on the effect of dopant concentration on morphology, structural, resonance and magnetic properties of NiO nanoparticle by varying the Fe concentration from 0.01 to 0.10 M. The synchrotron-x-ray diffraction confirmed that no secondary phase was observed other than NiO. The x-ray photoelectron spectroscopy studies revealed that, Fe was primarily in the trivalent state, replacing the Ni 2+ ion inside the octahedral crystal site of NiO. The Electron paramagnetic studies revealed the ferromagnetic cluster formation at high doping concentration (5 and 10%). The ZFC–FC curves displayed an average blocking temperature around 180 K due to particle size distribution. The anomalous behaviour of spontaneous exchange bias ( H SEB ) and magnetic remanence ( M r ) for all Fe-doped samples observed at 5 K showed an increase (0.1316–0.1384 emu g −1 ) in the moment of frozen spin ( M p ) as the dopant concentration increased. The role of frozen spin moment in spontaneous exchange bias behaviour was discussed.